2007
DOI: 10.1007/s00464-007-9244-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic parastomal hernia repair is feasible and safe: early results of a prospective clinical study including 55 consecutive patients

Abstract: Background: Parastomal herniation is a common complication, and its operative treatment is notoriously difficult. Recently, the authors have described a laparoscopic technique for closure and reinforcement of the hernia with a hand-made ''funnel-shaped'' Gore-Tex Dual Mesh. Potentially this technique combines the advantages of a mesh repair with those of minimal invasive surgery. Methods: In 2002, a multicenter trial of this new technique was started in The Netherlands. To date, 55 consecutive patients (27 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 21 publications
4
39
0
3
Order By: Relevance
“…The colon is involved by the defect in the prosthesis and it is fixed to the aponeurosis 15 . In both techniques, the mesh should be set to overcome the defect circumferentially in at least 5 cm.…”
Section: Laparoscopic Repairmentioning
confidence: 99%
“…The colon is involved by the defect in the prosthesis and it is fixed to the aponeurosis 15 . In both techniques, the mesh should be set to overcome the defect circumferentially in at least 5 cm.…”
Section: Laparoscopic Repairmentioning
confidence: 99%
“…Im Jahr 2007 wurde die erste größere Se rie zur Schlüssellochtechnik publiziert [7]. Die Rezidivrate war erstaunlich gering, die Nachbeobachtungszeit betrug aller dings nur 6 Wochen.…”
Section: Schlüssellochtechnikunclassified
“…Parastomal hernia surgery has been my principal point of interest for many years. In their discussion, the authors refer incorrectly to two of my publications [2,3].…”
mentioning
confidence: 99%
“…No modification of the technique was performed, and no open technique was described. Rather, as the title of the publication indicates, this is a publication of the short-term results of a prospective clinical study on 55 consecutive patients operated solely by laparoscopy [2]. It was concluded that the laparoscopic keyhole technique is a safe and feasible technique to repair parastomal hernias.…”
mentioning
confidence: 99%